AB0114 Comparative Analysis of the Expression of Protein Tyrosine Phosphatase Non-Receptor Type 2 (PTPN2) in Autoimmune Disease. (10th June 2014) - Aradi, B.; Armaka, M.; Filková, M.; Kato, M.; Klein, K.; Scharl, M.; Michel, B.A.; Senolt, L.; Gay, R.E.; Buzás, E.I.; Kollias, G.; Gay, S.; et al.
Abstract : Background: Protein Tyrosine Phosphatase Non-receptor Type 2 (PTPN2) is a phosphatase that plays an important role in inhibiting T-cell activation. The PTPN2 gene contains SNPs that are risk factors for the development of rheumatoid arthritis (RA), Crohn's disease and type 1 diabetes. We have previously shown that PTPN2 expression is elevated in RA synovial fibroblasts (RASF) compared to osteoarthritis synovial fibroblasts (OASF). Objectives: PTPN2 expression in peripheral blood mononuclear cells (PBMC) from patients with RA, OA, ankylosing spondylitis (AS) and systemic lupus erythematosus (SLE) was analyzed and compared to those from healthy subjects. Furthermore, we aim to analyze the inflammation-induced expression of PTPN2 in synovial fibroblasts from patients with RA and compare it with the expression in the TNF transgenic mouse model. Methods: PBMC were isolated using Ficoll-Paque (healthy controls n=5, OA n=1, RA n=5, AS n=6, SLE n=7)and either lysed directly or cultured and stimulated with tumor necrosis factor α (TNFα, 10 ng/ml, 24 h). Synovial fibroblasts were obtained from RA patients undergoing surgery and from the TNF transgenic mouse model. SF were stimulated with TNFα (10 ng/ml, 24 h or 1 week). Levels of PTPN2 mRNA were measured using TaqMan Real-time PCR. Western blot was used to measure PTPN2 protein levels. Results: PTPN2 is expressed in PBMC, however, no significant changes were found in the expression of PTPN2 in PBMC from autoimmune diseases (dCt ± SD, healthy controls 3.98±0.97, OA 4.00±0.0, RA 4.28±0.39, AS 4.06±0.54, SLE 4.05±0.48) In PBMC from healthy controls, stimulation with TNFα (10 ng/ml, 24h) did not increase the levels of PTPN2 (n=4, dCt ± SD unstimulated 4.18±0.3, TNF 4.23±0.8). Basal levels of PTPN2 were higher in RASF compared to OASF (mRNA: 1.6 fold, p<0.01; protein: 2.0 fold, p<0.05). After 24h of stimulation with TNFα, PTPN2 expression increased on the mRNA level (3.1 fold, p<0.05), as well as on the protein level (1.7 fold, p<0.05, n=7). Moreover, PTPN2 protein levels were also upregulated after long term stimulation with TNFα (10 ng/ml, 1 week, 2.4 fold, n=3). Increased protein levels were observed in both the 45 kDa and 48 kDa isoforms of PTPN2 after the short and long-term stimulation with TNFα. Most interestingly, SF from the TNFα transgenic mouse model show a higher expression of PTPN2 compared to wild type mice (TNFα transgenic mice n=4, wildtype mice n=5, ddCt of medians=-0.96). Conclusions: In the current study we show that PTPN2 expression is elevated in RASF but it is not changed in PBMC. Since we have previously shown that PTPN2 negatively regulates inflammation in RASF, we conclude that PTPN2 is a local regulator in the affected inflamed joints but not a modulator of systemic inflammation. Acknowledgements: IMI BTCure, IAR, EURO-TEAM Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4212